Considerations for determining the efficacy of new antiseizure medications in children age 1 month to younger than 2 years. Issue 10 (12th August 2022) - French, Jacqueline A.; Cleary, Elena; Dlugos, Dennis; Farfel, Gail; Farrell, Kathleen; Gidal, Barry; Grzeskowiak, Caitlin L.; Gurrell, Rachel; Harden, Cynthia; Stalvey, Tracy J.; Tsai, Julia; Wirrell, Elaine C.; et al.
Abstract: Objectives: Drug treatment for children with epilepsy should, ideally, be governed by evidence from adequate and well‐controlled clinical studies. However, these studies are difficult to conduct, and so direct evidence supporting the informed use of specific drugs is often lacking. The Research Roundtable for Epilepsy (RRE) met in 2020 to align on an approach to therapy development for focal seizures in children age 1 month <2 years of age. Methods: The RRE reviewed the regulatory landscape, epidemiology, seizure semiology, antiseizure medicine pharmacology, and safety issues applicable to this population. Results: After reviewing evidence, the conclusion was that pediatric efficacy trials would be impracticable to conduct but a waiver of the regulatory requirement to conduct any study would lead to an absence of information to guide dosing in a critical population. Review of available data and discussion of RRE attendees led to the conclusion that the requirements for extrapolation of efficacy from older children down to infants from age 1 month to <2 years old appeared to be met. After the RRE, the US Food and Drug Administration (FDA) approved brivaracetam for use in children with focal epilepsy above the age of 1 month in August 2021 and lacosamide in October 2021, both based on the principle of extrapolation from data in older children. Significance: These recommendations should result in more rapid accessibility of antiseizure medications for infants.